MAPPING THE WATER QUALITY STATUS AND POLLUTION LOAD OF SELOATAP RIVER IN GALENGDOWO VILLAGE, WONOSALAM, JOMBANG - Adityo Tri Wicaksono; Eko Rachmanu Handriyono (Journal of Applied Sciences, Management and Engineering Technology, 2020)
Seloatap River is a creek of Brantas River passing through Galengdowo Village, Wonosalam District, Jombang Regency. The majority of people in this area work as farmer and cowman. Unfortunately, its waste of farming has not been well-managed yet. Therefore, a study on the status of river water quality by IP (Index of Pollution) method based on The Ministerial Decree of Environment No. 115 in 2003 and The Government Regulation No. 82 in 2001 is necessary. This research aimed at mapping the results of analyzing the water quality status and pollution load of Seloatap River. This research was carried out in three phases i.e. preliminary survey, river water sample collection, and data analysis. The preliminary survey was for investigating Galengdowo Village location, pollutant type entering the river, river location, and coordinate data collection when the water of Seloatap River was taken. Meanwhile, the sample collection aimed at investigating the pollutant contents that were tested by some parameters namely DO, pH, TSS, BOD, COD, and Total Ammonia (NH3-N). The last, data analysis was for analyzing the obtained data to yield a map. The results of research demonstrated that the calculation using IP method gained from 0.63 (fulfilled the quality standard) to 5.33 (medium pollution).  Accordingly, the mapping process of pollution load and water quality status of Seloatap River indicated that this river was in polluted condition and had high pollution load resulted from farming sector.